RANCANG BANGUN AUTOCLAVE MENGGUNAKAN SENSOR SUHU DS18B20 DENGAN KONTROL RELAY BERBASIS ARDUINO - Zainal Arifin; Rizal Thalib (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2020)
The purpose of this final project is to design an Autoclave using a DS18B20 Temperature Sensor with Arduino Uno-based Relay Control. This autoclave uses a DS18B20 temperature sensor which functions to measure the temperature inside the tool. The usage is enough by setting the required temperature and timer, the temperature and timer that are set can be seen on the LCD display. The design method used in making the Autoclave design uses a DS18B20 Temperature Sensor with Arduino Uno-based Relay Control as a whole through 4 stages: (1) Selection of the components needed in the manufacturing process; (2) Component Installation; (3) Program Charging on Arduino; (4) Testing Tools and Drawing Conclusions. The performance test results show that the medical equipment will be sterile at 121 C for 10 – 15 minutes. If the temperature does not reach 121 C and the time is less than 10 minutes, then medical equipment cannot be said to be sterile. This sterilization test uses autoclave tape paper as an indicator. If the paper turns a faint brown color, it can be concluded that the medical equipment is not sterile, and if the paper changes color to blackish brown then the medical equipment is declared sterile. The advantage of this tool is that when the temperature reaches the setting, the buzzer will sound, and if the timer is set to run out or the sterilization process is complete, the buzzer will sound again.